1996
DOI: 10.1007/bf02915660
|View full text |Cite
|
Sign up to set email alerts
|

Intermixing model of continuous casting during a grade transition

Abstract: To investigate the composition distribution that develops in continuously-cast steel during a grade change, an efficient, accurate, and user-friendly computational model has been developed. The model is fully transient and consists of three submodels, which account for mixing in the tundish, mixing in the liquid core of the strand, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 4 publications
1
37
0
1
Order By: Relevance
“…In order to predict the final composition distribution within the final product, a further model must account for the cessation of intermixing after the shell has solidified. [133][134][135][136] Figure 11 shows example composition distributions in a continuous cast slab calculated using such a model. 133,134) To ensure accuracy, extensive verification and calibration were undertaken for each submodel.…”
Section: Solute Transport Phenomenamentioning
confidence: 99%
“…In order to predict the final composition distribution within the final product, a further model must account for the cessation of intermixing after the shell has solidified. [133][134][135][136] Figure 11 shows example composition distributions in a continuous cast slab calculated using such a model. 133,134) To ensure accuracy, extensive verification and calibration were undertaken for each submodel.…”
Section: Solute Transport Phenomenamentioning
confidence: 99%
“…Turbulent flow within the liquid pool may bring mixed molten steel far below the position of the meniscus. Huang and Thomas 10,11) have simulated the composition difference between the center and the surface in a section of the mixed zone according to the casting speed. They found that a slower casting speed greatly reduces the extent of mixing in the strand.…”
Section: Extending Cho and Kim's Tundish Model To The Strandmentioning
confidence: 99%
“…Pioneers in the area of developing an efficient intermixing model to predict the mixed region during a grade transition, Huang and Thomas 10,11) have developed a model for predicting the intermixed region within several seconds as opposed to the conventional methods that used to take several days or even weeks. Their model is designed to consider the mixing within both the tundish and the strand.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on the casting transition process have been reported. Huang and Thomas 30,31) developed a mathematical model, using a three-dimensional fluid flow model and one-dimensional mixing at various places in the tundish and strand. Cho and Kim 32) investigated the steel grade transition in a tundish using both water model and numerical simulation.…”
Section: Steel Grade Change Processmentioning
confidence: 99%